2020
DOI: 10.1002/jbm4.10393
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Methotrexate, Sulfasalazine, and Hydroxychloroquine Use With Fracture in Postmenopausal Women With Rheumatoid Arthritis: Findings From the Women's Health Initiative

Abstract: This study was conducted to evaluate the extent to which disease-modifying antirheumatic medications (DMARDs) used as part of a triple therapy for the treatment of rheumatoid arthritis (RA) including methotrexate, sulfasalazine, and hydroxychloroquine are associated with fractures in postmenopausal women with RA. Incident fractures following use of methotrexate, sulfasalazine, and/or hydroxychloroquine in postmenopausal women with RA in the Women's Health Initiative were estimated by Cox proportional hazards u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…If methotrexate is not appropriate, sulfasalazine and leflunomide are recommended. Experiments in cell and animal models have shown that methotrexate induces bone turnover by decreasing the differentiation of osteoblasts, production of bone matrix, and expression of RANKL; however, the dose used in the treatment of rheumatoid arthritis has little influence on bone metabolism and the development of osteoporosis [ 34 ].…”
Section: Treatments Of Osteoporosis and Joint Damage In Rheumatoidmentioning
confidence: 99%
“…If methotrexate is not appropriate, sulfasalazine and leflunomide are recommended. Experiments in cell and animal models have shown that methotrexate induces bone turnover by decreasing the differentiation of osteoblasts, production of bone matrix, and expression of RANKL; however, the dose used in the treatment of rheumatoid arthritis has little influence on bone metabolism and the development of osteoporosis [ 34 ].…”
Section: Treatments Of Osteoporosis and Joint Damage In Rheumatoidmentioning
confidence: 99%
“…When tested on osteoblasts HCQ treatment was found to decrease human mesenchymal stem cells derived osteoblast differentiation and mineralization in vitro [35]. The WHI observational study in RA patients taking HCQ have not found a difference in fracture rate in comparison to HCQ non-users [27].…”
Section: Hydroxychloroquine-conflicting Resultsmentioning
confidence: 99%
“…BMD measurements of the children between 5 and 10 years showed that children whose mothers were treated with SSZ during pregnancy had a higher total body BMD [32] compared to children of mothers who were not treated with SSZ. Subsequent studies ,however, do not confirm any beneficial impact of SSZ on fracture risk [27].…”
Section: Sulfasalazine-likely Little Effect On Bone Healthmentioning
confidence: 95%
See 1 more Smart Citation
“…Those with family history and chronic inflam-mation as well as smokers are most often affected [3,4]. It is increasingly appreciated that RA is associated with substantial social burden, deceased life quality and comorbidities, including fracture and cardiovascular events [5,6]. In recent years, there has been growing awareness on the role of RA in the onset and development of cardiovascular diseases [7].…”
Section: Introductionmentioning
confidence: 99%